AN REVIEW ON NATURAL POLYMERS APPROACHES TO FLOATING DRUG DELIVERY SYSTEM - Mohan, Paresh; Doshi, Saurabh; Khinchi, M. P.; Sharma, Natasha; Agrawal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2013)
The purpose of writing this review on floating drug delivery systems (FDDS) was to compile the recent literature with special focus on the natural polymers used in mechanism of floatation to achieve gastric retention. Controlled and sustained released formulations are widely used in modern era for the delivery of various ingredients. D rugs with narrow absorption window in the gastrointestinal tract have poor absorption therefore gastro retentive drug delivery systems (GRDDs) have been developed which prolong the gastric emptying time. This review summarizes the study of various natural polymers which are used in floating drug delivery system. These natural or biodegradable polymers are very useful to reduced or minimizes the side effects of the drugs than those which are having combination with synthetic and semi -synthetic polymers. This review having lots of natural polymers like Guar gum, Tragacanth, Karaya gum, Copal gum, Dammar gum, Pectin, Na Alginate, Gelatin etc.